A free-space measurement of complex permittivity of natural rubber filled with carbon black at microwave frequency / Mohd Ilham Adam - Adam, Mohd Ilham (2004)
This project involves a free-space measurement system operating in the 7.5 - 12.5 GHz (X band) frequency range to measure the Reflection and Transmission Coefficients, Sn and S21, of the planar samples. It involves measurements of the Dielectric Constant of the Natural Rubber which filled with different concentration of Carbon Black (HAF N330). To eliminate the effect of Teflon, FORTRAN 77 computer program is used and the Complex Electric Permittivity is calculated from the measured values of the Reflection Coefficient, Sn and the Transmission Coefficient, S21 using Borland C++ computer program. Another method, the Complex Electric Permittivity is calculated from the measured values of the Transmission Coefficient, S21 only using FORTRAN 77 computer program. The measurement system consists of transmit and receive horn lens antennas, a vector network analyzer, computer and a printer. Diffraction effects at the edges of the samples are minimized by using spot- focusing lens antennas. Errors due to multiple reflections between antennas via the surface of the samples are corrected by using a free-space LRL (line, reflect, line) calibration technique. For flexible samples, the sample had to be sandwiched between two quarter-wavelength (at mid band) Teflon plates, to eliminate the effect of sagging. Because of the far-field focusing ability of horn lens antennas, free-space measurement can be made at microwave frequency in a relatively compact and simple measurement setup.